Crosstalk Between Coagulopathy and Inflammation in Obesity-Related Severe COVID-19 Infection - Talebabadi, Nazanin; Eusni Rahayu, Mohd Tohit; Abdullah, Maha; Siti Yazmin, Zahari Sham; Nur Fatin Zalikha, Zailan; Syafinaz, Amin Nordin; Irmi Zarina, Ismail; Ahmad Mahfuz, Gazali; Masriana, Hassan (MDPI, 2025)
Abstract: Obesity is among the most prevalent risk factors in the severe forms of Coronavirus disease 2019 (COVID-19) infection. COVID-19 patients with obesity often face severe complications that might be associated with overexpression of adiponectin, inflammatory cytokines, and angiotensin converting enzyme 2 (ACE2) receptors in visceral fat. The pre-existing subclinical inflammation associated with obesity can also lead to severe inflammatory responses. Elevation of proinflammatory cytokines considerably activates coagulation cascades, including the tissue factor (TF) pathway. The hypercoagulable state in COVID-19 is presented with severe pulmonary complications such as venous thromboembolism (VTE), disseminated intravascular coagulation (DIC), and disruption of vascular endothelial cells, which can lead to severe complications and death. The interaction between inflammatory response and coagulation mechanism in COVID-19 patients with obesity warrants a further understanding of prognosis and potential therapeutic approaches. This review discusses the crosstalk between inflammation and coagulopathy in obesity-related severe COVID-19 infection.